Valor nutritivo do pasto de Urochloa brizantha cv Marandu em diferentes épocas do ano - Fernandes, Geferson Antonio (2016)
The tropical forages have high dry matter production, with marked seasonality between stations the "wet" and "dry". This seasonality determines uneven distribution of production throughout the year, and the beginning of their reproductive period in which changes occur between the appearance and mortality rates of tillers. In the region of the Midwest can observe four well-defined seasons that change the chemical composition of the forage being :, rainy season, transition water-dry, dry, dry water. These different periods make occurring qualitative and quantitative changes in the chemical composition of plants, resulting in lower quantity and quality in periods where there is less rainfall. The variability of nutritional value among species and cultivars is extremely large, as the largest changes occur in the characteristics associated with maturation of the plant, such as protein, minerals, cell wall. As the plant matures crude protein, minerals and other cellular contents of the components decrease, while the increase of the cell wall. The Marandu grass concentrates most of its dry matter production during the rainy season, mainly as a result of climatic factors such as temperature and rainfall. In the case of animal production, the FDN and FDA are related to the intake and digestibility of forage. The FDA is directly related to rumen fill effect and inversely the energy concentration of the diet of cattle. The digestibility of organic matter (OM) is another factor that is highly correlated with the voluntary intake, as it will facilitate the process of degradation and passage of the forage through the digestive tract. Low forage digestibility results in higher retention time in the rumen, promoting physical order of consumption limitations. when analyzing the fractions of the crude protein of forages are observed, often, higher values of fractions A, non-protein nitrogen, B2, true protein (intermediate degradation) and B3, slow degradation protein, associated with the fiber. This protein degradability determines the availability of nitrogenous compounds in the rumen for microbial protein synthesis, and thereby increases the availability of microbial origin amino acids in the intestine. Before that objective with this study was to evaluate the nutritional value of pasture of Urochloa brizantha Marandu in different seasons and these, dry, dry-water transition, water and transition dry-water.